The Relationship Between The Quality Of Service Of Bpjs Patients In Class Iii Inpatient Rooms With The Level Of Satisfaction At Hassanudin Damrah Hospital Manna - Sari, Rina Polama Okta; Novega, Novega; Fitrizah, Miki Kurnia (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Background: Hospitals are health service facilities that aim to provide complete individual health services, focusing more on health promotion and prevention efforts without ignoring curative-rehabilitative efforts that provide inpatient, outpatient and emergency services. In health services in hospitals, one indicator of the success of health services is patient satisfaction. Patient satisfaction is the result of patient opinion and assessment of the performance of services provided by health service facilities. Patient satisfaction is a reflection of the quality of health services. Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services obtained after the patient compares it with what he expected. There were 4 patients who were dissatisfied with patient service. Patient dissatisfaction is due to the poor hospital environment and staff who are less friendly in providing health services to patients. The general aim of this research is to determine the relationship between the quality of BPJS patient services in class III inpatient rooms and the level of satisfaction at Hassanudin Damrah Manna Hospital. Method: This research uses a correlational quantitative approach to find the relationship between the quality of BPJS patient services in Class III inpatient rooms and the level of satisfaction at Hassanudin Damrah Manna Hospital which was carried out from 1 September to 31 September 2024 and a sample of 82 respondents. The research results showed that the majority of BPJS patients in Class III treatment rooms, namely 58.8% stated that the officers' responsiveness was good, 50% stated that health assurance (guarantee) was good, 59.8% stated that Tangible (Physical Evidence) was good, 62 .2% said the officer's empathy was good and 59.8% said the officer's reliability was good. This research can provide suggestions to Hassanudin Damrah Manna Hospital to improve patient satisfaction services.